Antagonic Activity of Endophytic Bacteria Isolated from Man Trau Grass on Stem Rot Disease Of Pitaya (Hylocereus Undatus) - Trung, Do Quang; Thu Hang, Nguyen Thi; Van, Dinh Mai; ngoc, Pham Bich Bích; Hang, Tran Thi; Anh, Luu The; Tien, Phi Quyet (VNU Journal of Science: Natural Sciences and Technology; Vol 37 No 2DO - 10.25073/2588-1140/vnunst.5125, 2021)
Endophytic bacteria reside in the intercellular spaces in different plant tissues without causing damage. This study aimed to select endophytic bacterial strains from Man Trau grass (Eleusine indica) that are able to inbibit the fungus A. alternata  causing stem rot disease on pitaya. The result showed that one fungal isolate was pathogenic and caused stem rot disease on dragonfruit. The analysis results based on morphological characteristics and ITS region sequence indicated that the isolated fungal strain is 100% identical to A. alternata. In addition, a total of 16 endophytic bacterial strains were isolated from Man Trau grass samples in Binh Thuan and screened for antifungal activity. Ten bacterial strains with antagonistic activity against A. alternata causing stem rot disease on pitaya were detected. Among those, strain MT47 showed the strongest antifungal activity with an efficiency of 36.67%. Moreover, the result also presented that the antagonistic strain MT47 pocesses the ability of biofilm formation significantly higher than the control. The results suggest that these endophytic bacteria can be used in biocontrol of the stem rot disease on pitaya.